Penurunan Skala Nyeri Rheumatoid Arthritis dengan Terapi Simple Reminiscance - Fatsiwi Nunik Andari; Andri Kusuma Wijaya (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2022)
Background: Rheumatoid arthritis is a chronic systemic inflammatory disease with the main manifestations of progressive polyarthritis and involving all organs of the body. The negative impact of this disease has a significant effect on the ability to carry out activities, both in terms of work or in household tasks, resulting in an increase in socio-economic costs, and can impact the quality of life and life expectancy of the sufferer. Methods: This research is a type of quasy experiment research with one group pre and post test design. Results: The highest level of pain before being given Simple Reminiscence therapy intervention was moderate pain level (71.4%) and after being given intervention the level of pain felt by respondents was mild pain level (100%). Based on the results of the Paired Test, it was obtained that p-value = 0.000 which means significant, so it can be concluded that there is an effect of providing Simple Reminiscence therapy intervention on reducing the level of rheumatoid arthritis pain in the elderly at the Panti Sosial Tresna Werdha., Bengkulu City.Keywords: pain, rheumatoidÂ arthritis, simple reminiscence therapy